ENVIRONMENTAL AND SOCIAL INFORMATION DISCLOSURE QUALITY AND FINANCIAL PERFORMANCE OF LISTED MANUFACTURING COMPANIES IN NIGERIA - Saka Tunde Abdulsalam (Gusau Journal of Accounting and Finance)
The General perception of investors and other stakeholders is that self-developed environmental and social information disclosure (ESID) of companies lack quality required to make informed business decision which may impact company operating cash flow (OCF). Although, poor quality ESID often damaged company reputation and cause competitive setback that usually bring down OCF. Based on this backdrop, this study explores ESID quality of Listed Manufacturing Companies in Nigeria (LMCN) based on Global Reporting Initiative (GRI) and evaluate the impact on their OCF. The study employs Ex-Post Facto research design and data collected from annual reports of forty-seven LMCNs were analyzed using panel regression analysis based on random effect model. While quality of ESID of companies were measured based on GRI sustainability quality principle such as Balance, Clarity, Timeliness, Relevance, Reliability and Comparability, financial performance (FP) was measured by OCF of the studied companies. Findings from regression result revealed that quality of environmental and social information disclosure displays a significant and positive correlation with OCF. This study concluded that substantive investment in sustainability activities and quality disclosure is a form of undisputed contribution to sustainable development that in turn provide a basis for securing enhanced FP. This study recommends that manager should henceforth, consider potential returns that will come from investment in substantive environmental and social activities and quality disclosure that follow GRI quality reporting principle.